Growth and Production of Kailan (Brassica oleraceae L.) with Application of Banana Waste Liquid Organic Fertilizer and Cow Manure - Rizky, Arya Alfa; Manurung, Adinda Nurul Huda; Azmi, tubagus Kiki Kawakibi; Malasari, Silvina (International Journal on Food, Agriculture and Natural Resources, 2025)
Kailan (Brassica olerace L.) is one of the popular vegetables in Indonesia. Vegetable cultivation should use environmentally friendly fertilizers, such as cow manure and banana waste liquid organic fertilizer (BWLOF). This study aims to analyze kailan's growth and production responses with differences concentration and dose in liquid organic fertilizers from banana waste and cow manure, respectively. This study used a factorial Randomized Complete Block Design (RCBD) consisting of 2 factors, namely banana waste liquid organic fertilizer (BWLOF) with concentrations of 0, 20, and 40 ml L-1 and cow manure (K) with doses of 0, 127, and 200 g/polybag. The results of the orthogonal polynomial test showed that the optimum concentration of BWLOF for kailan was 12.4 ml L-1, and the results of the DMRT test showed that dose of 200g polybag-1 of manure was the best treatment to increase the growth of kailan. The conclusion of this study showed that the provision of BWLOF significantly increased the root length and total dry weight of kailan plants. The provision of cow manure significantly impacted in increasing plant height, number of leaves, stem diameter, leaf area, root length, and fresh and dry weight in the crown and roots, including the root crown ratio. However, there was no interaction between BWLOF and cow manure, which suggests that their combined use may not necessarily lead to synergistic effects.